Empowring Farmer Cooperatives Through Sustainable Cacai Fermentation And Processing Training In Central Sulawesi - Muh Nur; Pong Krit; Siri Lek (Yayasan Adra Karima Hubbi, 2025)
Background. Smallholder cocoa farmers in Central Sulawesi continue to face persistent challenges related to low product quality, weak post-harvest management, and limited value addition, which collectively reduce their competitiveness in both domestic and international markets. One critical bottleneck lies in inadequate fermentation and processing practices at the cooperative level. Purpose. This study aims to empower farmer cooperatives through sustainable cocoa fermentation and processing training to improve product quality, institutional capacity, and farmers’ economic resilience. Method. The research employed a participatory action research approach, integrating training workshops, hands-on demonstrations, mentoring, and pre–post evaluations involving members of selected farmer cooperatives. Data were collected through observations, interviews, focus group discussions, and quality assessment of fermented cocoa beans. Results. The results indicate significant improvements in farmers’ knowledge and skills related to standardized fermentation techniques, hygiene, and post-harvest handling. Cooperatives demonstrated enhanced consistency in fermentation quality, improved bean aroma and appearance, and increased awareness of sustainability principles. Moreover, institutional strengthening was observed through better collective management and decision-making within cooperatives. Conclusion. In conclusion, sustainable fermentation and processing training effectively empowers farmer cooperatives by improving cocoa quality and reinforcing cooperative capacity, thereby contributing to higher market value and long-term livelihood sustainability for cocoa farmers in Central Sulawesi.